Spontaneous Transformation of Murine Oviductal Epithelial Cells: A Model System to Investigate the Onset of Fallopian-Derived Tumors - Endsley, Michael P.; Moyle-Heyrman, Georgette; Karthikeyan, Subbulakshmi; Lantvit, Daniel D.; Davis, David A.; Wei, Jian-Jun; Burdette, Joanna E. (Frontiers in Oncology, 2015)
High-grade serous carcinoma (HGSC) is the most lethal ovarian cancer histotype. The fallopian tube secretory epithelial cells (FTSECs) are a proposed progenitor cell type. Genetically altered FTSECs form tumors in mice; however, a spontaneous HGSC model has not been described. Apart from a subpopulation of genetically predisposed women, most women develop ovarian cancer spontaneously, which is associated with aging and lifetime ovulations. A murine oviductal cell line (MOELOW) was developed and continuously passaged in culture to mimic cellular aging (MOEHIGH). The MOEHIGH cellular model exhibited a loss of acetylated tubulin consistent with an outgrowth of secretory epithelial cells in culture. MOEHIGH cells proliferated significantly faster than MOELOW, and the MOEHIGH cells produced more 2D foci and 3D soft agar colonies as compared to MOELOW. MOEHIGH were xenografted into athymic female nude mice both in the subcutaneous and the intraperiteonal compartments. Only the subcutaneous grafts formed tumors that were negative for cytokeratin, but positive for oviductal markers such as oviductal glycoprotein 1 and Pax8. These tumors were considered to be poorly differentiated carcinoma. The differential molecular profiles between MOEHIGH and MOELOW were determined using RNA-Seq and confirmed by protein expression to uncover pathways important in transformation, like the p53 pathway, the FOXM1 pathway, WNT signaling, and splicing. MOEHIGH had enhanced protein expression of c-myc, Cyclin E, p53 and FOXM1 with reduced expression of p21. MOEHIGH were also less sensitive to cisplatin and DMBA, which induce lesions typically repaired by base-excision repair. A model of spontaneous tumorogenesis was generated starting with normal oviductal cells. Their transition to cancer involved alterations in pathways associated with high-grade serous cancer in humans.